Faktor Pengelolaan Operasi dan Pemeliharaan Irigasi di Kabupaten Tanah Datar - Yuni Purnama Syafri; Barkhia Yunas; Juwita Wirta Sri Devi; Hanafi Malik (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
Based on the Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 14/PRT/M/2015 concerning Criteria and Determination of Irrigation Area Status, Tanah Datar Regency has 635 regency Irrigation Area authorities with a total Irrigation Area of ​​29,437 Ha. Over the last 5 years, the Tanah Datar Regency Government, especially the PUPR and Land Services Department, has allocated funds both from the APBN (DAK) and from the APBD (DAU) for the construction and rehabilitation of irrigation networks as well as improving irrigation networks, with the result that the irrigation conditions in Tanah Datar Regency are in good condition. good by 56.69%, in other words as many as 379 irrigation areas which were only in good condition were maintained in poor condition. The aim of this research is to determine the factors of irrigation maintenance and upkeep operations in Tanah Datar Regency by looking at six aspects of irrigation network maintenance and rehabilitation. The method used in this research is a qualitative descriptive method. Primary data was taken through interviews with informants from the Public Works and Spatial Planning and Land Service of Tanah Datar Regency, Tanah Datar Regency in the Water Resources sector, namely the Sub-coordinator of the Tanah Datar Regency irrigation Maintenance Operations. The research results show that there are 2 (two) factors that influence Irrigation Operations and Maintenance, namely (1) Condition factors of physical infrastructure and supporting facilities, (2) Personnel and institutional organizational factors of P3A.